Is poor director attendance contagious?. Issue 1 (February 2018) - Nowland, John; Simon, Andreas
Recent corporate governance guidelines have focused on the structure of the board of directors, with little recognition of the importance of director attendance at board and committee meetings. Director attendance is vital as prior studies show that director absences result in weaker monitoring of management and lower firm performance. This study examines whether directors learn from the attendance behavior of their board colleagues, thereby magnifying the scope and potential consequences of good or poor attendance practices. We find that director attendance is significantly positively related to their board colleagues attendance, including colleagues in the same firm and colleagues in other firms where the director holds other directorships. For policymakers, these results indicate that ongoing attention needs to be paid to the attendance practices of directors, with intervention required to ensure poor attendance practices do not become contagious.